Synthesis and cathodic properties of LiCo1-yRhyO2 (0≤y≤0.2) and LiRhO2 - Chowdari, Bobba V. R. (2014)
Compounds of the formula LiCo12yRhyO2 (0.0 ≤ y ≤ 0.20 and y=1.0) have been synthesized by high temperature solid-state reaction and characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy, and infrared spectroscopy. Single-phase materials were obtained for y ≤ 0.10 and y=1.0 as observed by XRD. However, IR and electrochemical data indicate that the true solid solubility may be y ≤ 0.05. Their cathodic behavior in coin cells with Li metal as anode and a liquid electrolyte has been examined. Cyclic voltammograms and galvanostatic charge/discharge curves show that for y = 0.05, the phase transformation occurring at x = 0.5 in Li1-xCoO2 is suppressed and the deintercalation voltage is decreased. The compositions with y = 0.05 and 0.10 show improved cathodic behavior and discharge capacity retention compared to LiCoO2 (y = 0) at 0.14C rate in the voltage range 2.7-4.3 V up to 18 cycles. Electrochemical studies on LiRhO2 show that phase transitions occur on charge/discharge cycling (varying x in Li12xRhO2) in the voltage window 3.2-3.7 V and these are reversible. This compound shows an initial charge capacity of 162 mAh/g when charged to 4.0 V (vs. Li metal), corresponding to x = 0.85 in Li1-xRhO2. After an initial loss of 40 mAh/g in capacity, the discharge capacity retention corresponds to 90% after 18 cycles with respect to the initial discharge capacity in the voltage window, 2.7-4.0 V.